2020
DOI: 10.1111/tbed.13467
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and prevalence of porcine circovirus type 3 (PCV3) and type 2 (PCV2) in the Midwest of the USA during 2016–2018

Abstract: In recent years, reports indicated that PCV3 may be involved in porcine dermatitis and nephropathy syndrome (PDNS)-like disease similar to that linked to PCV2.A total of 2,125 porcine samples from 910 cases were collected during 2016-2018 and tested for presence of PCV3 and PCV2 by real-time PCR assays. Results showed high prevalence of PCV3 and PCV2: 28.4% samples from 41.2% cases were PCV3 positive and 16.4% samples from 16.7% cases were PCV2 positive. The overall coinfection rate was 5.4% and 8.4% at the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(102 citation statements)
references
References 37 publications
5
81
3
Order By: Relevance
“…Based on our previous study ( Wang et al, 2019b ), PCV2 strains were separated into 12 clusters, namely Cluster 1–12, by phylogenetic analysis; Cluster 8, Cluster 3 and Cluster 1 corresponded to genotypes, PCV2a, PCV2b and PCV2d, respectively. The three genotypes were identified as common strains currently circulating in the USA ( Wang et al, 2019b ; Xiao et al, 2016 ). An unrooted phylogenetic tree generated with PCV2 ORF2 sequences indicated that the three genotypes grouped into three separate clusters ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on our previous study ( Wang et al, 2019b ), PCV2 strains were separated into 12 clusters, namely Cluster 1–12, by phylogenetic analysis; Cluster 8, Cluster 3 and Cluster 1 corresponded to genotypes, PCV2a, PCV2b and PCV2d, respectively. The three genotypes were identified as common strains currently circulating in the USA ( Wang et al, 2019b ; Xiao et al, 2016 ). An unrooted phylogenetic tree generated with PCV2 ORF2 sequences indicated that the three genotypes grouped into three separate clusters ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The sequence dataset was established from our previous study ( Wang et al, 2019b ). Briefly, all available PCV2 ORF2 sequences were downloaded from the GenBank database (https://www.ncbi.nlm.nih.gov/genbank/).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…At least four commercial PCV2a vaccines have been widely used to reduce viremia and PCV2 infectious pressure in swine herds [12][13][14][15]. That might have caused the global trend shift from PCV2a to PCV2b first [16][17][18][19], and then PCV2d (PCV2b mutant strain) has become a predominant genotype globally [20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%